Perbandingan Analisis Struktur Dan Sifat Mekanik Material Komposit Dari Weave Carbon Fiber & Chopped Carbon Fiber - Jamil, Khoirul Fajril; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
In this paper, the structure and mechanical properties of Weave Carbon Fiber and Chopped Carbon Fiber are compared. Both of these carbon fibers are used as composite materials for defense equipment and automotive materials applications. Weave Carbon Fiber is a regular woven carbon fiber structure, which provides high tensile strength and elasticity, making it suitable for applications that require structural stability and balance as well as resistance to deformation. On the other hand, Chopped Carbon Fiber is short fibers entangled in the matrix and distributed randomly so that it has a better level of impact resistance but lower tensile strength. 2D manufacturing involves tensile testing, flexural testing, impact testing, and hardness measurements Strain 2D Weave Carbon Fiber has a strength of up to 500 MPa and an elastic modulus of up to 25 GPa, making it suitable for applications that require high mechanical strength Fiber fraction test Chopped Carbon Fiber shows the highest fiber fraction impact resistance of 1668 J/m at 8% fiber fraction but decreases at high fiber fraction. Weave Carbon Fiber has small deflection and good load resistance compared to Chopped Carbon Fiber. This journal can provide insight into the selection of the right material for industries that require high-strength but also lightweight materials. As planned, the selection of such materials is largely determined by the specific application desired.